Pengaruh Prenatal Yoga Terhadap Pengurangan Keluhan Pada Ibu Hamil - Dika Yanuar Frafitasari; Ayu Rosita Dewi; Pety Merita Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Women during their 9 months of pregnancy will experience many changes, both physical changes and psychological changes. Changes that occur often cause discomfort and complaints in pregnant women. Physical changes that occur may include breathing problems, sleep disturbances, gingivitis and redness of the gums, frequent urination, an uncomfortable feeling in the perineum, back pain, constipation, varicose veins, easy fatigue, false contractions, leg cramps, and ankle edemagivitis and redness of the gums, frequent urination, an uncomfortable feeling in the perineum, back pain, constipation, varicose veins, easy fatigue, false contractions, leg cramps, and ankle edema. This study aims to determine the effect of complementary therapy (pregnancy yoga or prenatal yoga) on reducing complaints experienced by mothers during pregnancy. 1 In this study, an analytic survey with a cross-sectional observational design was used. The sampling technique uses purposive sampling. The sample size in this study was 49 respondents. This research was conducted in September–November 2022. The statistical analysis used in this study was the linear regression test. Based on the results of statistical tests, more than two complaints of pregnant women can be reduced by the number of mothers who often do prenatal yoga, namely as many as 48% of respondents with p < (0.005). The conclusion in this study is that there is an effect of prenatal yoga on reducing complaints in pregnant women. It is recommended for pregnant women to empower themselves by doing prenatal yoga exercises to achieve a healthy and comfortable pregnancy and childbirth.